Protest, social movements, and global democracy since 2011 : new perspectives - Davies, Thomas Richard; Ryan, Holly Eva; Pena, Alejandro Milciades (Research in social movements, conflicts and change ;, 2016)
In light of the limited achievements of the Arab Spring and other pro-democracy movements, volume 39 examines and unpacks arguments that these protests represent both a new phase and new prospects for democratic mobilization. The volume engages with new theoretical and methodological perspectives and illuminates novel aspects of transnational social movement dynamics, such as the evolving role of information technology, deterritorialisation and government counter-responses.